IMPACT OF HR PRACTICES ON EMPLOYEE SATISFACTION IN STAFFING AGENCIES - Malakar, Nishit N.; Chakravorty, J. N. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The impact of employee satisfaction on the success of staffing agencies is significant, as it directly affects employee productivity, retention, and overall organizational performance. Of the five HR functions investigated in this study, recruitment had the most positive impact on employee satisfaction, suggesting that the recruitment function in staffing agencies plays a significant role in influential employee satisfaction levels. Using a mixed-method approach, we collected data from employees working in staffing firms through surveys and interviews. Conclusion: Well-designed HR policies, transparent communication and career growth prospects play a major role in employee gratification, the findings suggest. But, job security and huge attrition still plague staffing industry. Based on survey data which it analyzed, the study highlights the role of strategic HR initiatives focused on employee engagement, fair compensation, and continuous professional growth, through which staffing agencies could positively affect employee morale. This investigation adds to the mound of information on HR effectiveness in non-traditional employment sectors and delivers practical understandings for HR professionals and policymakers.